PENGARUH LATIHAN GAME SHOOTING TERHADAP KETERAMPILAN SHOOTING PADA TIM SEPAK BOLA SMAN 4 TAMBUSAI UTARA - Zaputra, Suherwan; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on observations made by researchers at the SMAN 4 Tambusai Utara football team, researchers looked at this soccer athlete, there were some athletes who were in the good category and almost all of these teams were not good at shooting during training or during matches. If this is not noticed, then the team will be difficult to win the match. This is seen when the player controls the ball and immediately shoots, and when the player has passed his opponent, the player is not able to shoot well from outside the penalty box. Based on the above problems the researchers sought to improve shooting skills at the SMU 4 Tambusai North football team through training shooting games. The population in this study were football team players, which amounted to 18 people from students of SMAN 4 Tambusai Utara. In the research the sampling technique used was total sampling, the instrument used to collect data was the agility test with pree test and post test shooting. The data analysis technique used was the t test. Based on the results of the research that has been obtained, it can be concluded that there is a positive and significant influence on the practice of shooting games on shooting skills with the results of the t test that t count = 6.736> from t table = 1.740. So that it is known that there is the effect of shooting game training on shooting skills on the SMA 4 Tambusai North football team.Key Words: Shooting Game Exercises, Shooting Skills